Genetic testing for haemochromatosis in patients with chondrocalcinosis. - Timms, A; Sathananthan, R; Bradbury, L; Athanasou, N; Wordsworth, B; Brown, M (2002)
Hereditary haemochromatosis (HH) is the most common lethal monogenic human disease, affecting roughly 1 in 300 white northern Europeans. Homozygosity for the C282Y polymorphism within the HFE gene causes more than 80% of cases, with compound heterozygosity of the C282Y and H63D polymorphism also increasing susceptibility to disease. The aim of this study was to determine the frequency of the C282Y and H63D polymorphisms in the disease, and to assess the risk of HH in heterozygotes for the C282Y polymorphism. 128 patients were recruited because of either radiographic chondrocalcinosis (at least bicompartmental knee disease or joints other than the knee involved) or CPPD pseudogout. Genotyping of the HFE C282Y and H63D mutations was performed using PCR/SSP and genotypes for the C282Y polymorphism confirmed by PCR/RFLP. Historical white European control data were used for comparison. Two previously undiagnosed C282Y homozygotes (1.6%), and 16 C282Y heterozygotes (12.5%), including four (3.1%) C282Y/H63D compound heterozygotes were identified. This represents a significant overrepresentation of C282Y homozygotes (relative risk 3.4, p=0.037), but the number of heterozygotes was not significantly increased. At a cost per test of pound1 for each subject, screening all patients with chondrocalcinosis using the above ascertainment criteria costs only pound64 for each case of haemochromatosis identified, clearly a highly cost effective test given the early mortality associated with untreated haemochromatosis. Routine screening for haemochromatosis in patients with appreciable chondrocalcinosis is recommended.